2022
DOI: 10.1080/08998280.2022.2028344
|View full text |Cite
|
Sign up to set email alerts
|

Relation between inflammatory bowel disease, depression, and inpatient outcomes in the United States

Abstract: The relationship between inflammatory bowel disease (IBD) and depression is complicated. The effect of depression on ulcerative colitis (UC) and Crohn's disease (CD) among the inpatient US population has not previously been studied. We retrospectively analyzed patients admitted with UC and CD from 2016 to 2019 using the National Inpatient Sample database. Our primary outcome was the effect of depression on hospital length of stay (LOS), costs, and mortality. Secondary outcomes included the comparison between U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In a similar study utilizing the KID on pediatric IBD patients, depression was associated with prolonged hospital stay with an odds ratio of 1.5 (1.19–1.90), p <0.01, while no significant association was noted between depression and procedures, imaging or need for surgery during the hospitalizations [ 20 ]. Another recent study evaluating depression in adult patients with both CD and UC also demonstrated similar results with higher length of hospital stay in patients with depression [ 21 ]. In our study, we found similar results that patients with depression and anxiety had 1.2 and 0.95 additional days of mean hospital stay respectively, after adjusting for other demographic factors and disease severity.…”
Section: Discussionmentioning
confidence: 62%
“…In a similar study utilizing the KID on pediatric IBD patients, depression was associated with prolonged hospital stay with an odds ratio of 1.5 (1.19–1.90), p <0.01, while no significant association was noted between depression and procedures, imaging or need for surgery during the hospitalizations [ 20 ]. Another recent study evaluating depression in adult patients with both CD and UC also demonstrated similar results with higher length of hospital stay in patients with depression [ 21 ]. In our study, we found similar results that patients with depression and anxiety had 1.2 and 0.95 additional days of mean hospital stay respectively, after adjusting for other demographic factors and disease severity.…”
Section: Discussionmentioning
confidence: 62%
“…The NIS has been used previously to report inpatient outcomes and to derive predictive scoring models [ 15 - 17 ]. Since the NIS contains de-identified patient data, it was deemed exempt from review as per institutional review board guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The threshold for statistical significance was kept at 0.05, with all P-values being 2-sided. For primary outcomes such as median length of stay (LOS) and median inpatient charges, we utilized weighted hierarchal linear regression models and adjusted for confounding variables, as previously reported [ 5 ]. We used hierarchal Cox regression models for inpatient mortality and adjusted for patient and hospital-level confounders, including discharge disposition, where indicated.…”
Section: Methodsmentioning
confidence: 99%
“…There is a reported higher prevalence of psychological disorders in IBD patients, concurrently associated with greater consumption of substances such as cocaine, cannabis, and opioids [ 5 , 6 ]. Consumption of these substances and alcohol can complicate the management of IBD.…”
Section: Introductionmentioning
confidence: 99%